The influence of stigma and depression on quality of life of leprosy patients - Jenny MC Siagian, Carla R Marchira Agnes S. Siswati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2009)
Background: Stigma attached to leprosy-affected individuals is one of the strongest stigma of diseases. Depression is often occurred to many lepers. Stigma and depression are two factors which affect the quality of life of the lepers. Objective: To determine whether stigma and depression affect the quality of life of leprosy patients in Dermatovenereology outpatient clinic at RSUP Dr Sardjito Hospital. Methods: It was a quantitative and cross-sectional research. The quantitative analysis was conducted with chi-square and multiple regression methods. Result: There was no significant correlation between stigma and quality of life of leprosy patients. The factors which significantly correlated with quality of life were gender, income, and depression score (p < 0.051. Depression score significantly affected the quality of life (B 1.876; P < 0.05; CI 1.166-36.5661. Conclusion: Depression affected the quality of life more than deformity and demographic factors among leprosy patients in Dermatovenereology outpatient clinic at RSUP Dr Sardjito Yogyakarta. Key words: stigma - depression - lepro